Monitory institutions, social activism, and the fifth estate: the case of David Hicks. Issue 4 (1st October 2016) - Fordham, Helen
ABSTRACT: During the early years of the blogosphere the fifth estate was conceptualised as networks of individual citizen bloggers who were independent of the structures and constraints of institutionalised power – and the other estates – and whose primary function was media criticism. An examination and analysis of the David Hicks' case, makes it evident, however, that the fifth estate was more complex than these early theorisations. By drawing upon the media coverage of Hicks' arrest, detention, and repatriation back to Australia, which played out in the mainstream media, political blogs, and special interest publications between 2002 and 2007, it becomes evident that the fifth estate during this period also consisted of networks of 'extra-parliamentary power monitoring institutions' (Keane 2009, p. xxvii). Human rights groups, political parties, and professional associations used the communicative power of both mainstream and digital media to monitor and critique power, and engage in debates about ethical accountability. These debates exposed how technology had ruptured the theoretical boundaries between the grassroots activism of citizens and the political advocacy of monitory institutions, and blurred the divide between citizen bloggers and journalists, producing the fifth estate as a politically potent and heterogeneous space.